Plenary Collaboration #2: Black Studies In and Around Romanticism - Aljoe, Nicole; Diaby, Bakary; Joseph-Gabriel, Annette (Romanticism on the Net, 2024)
This group of plenarists sought to think beyond the binaries of canon/noncanon or outside/inside and instead consider how Romanticism and the Romantic era might be reconfigured, stretched, and transformed by authors, queries, and methods that were a “little off” Romanticism proper (in 2021). Each plenarist focused their question around a particular question: Annette Joseph-Gabriel considered “How might Romanticism and Black Studies meet in other ways, in other speculative futures?”; Bakary Diaby asked “How might Black Studies help us as we reconfigure Romanticism as a site of vital contemporary scholarship, pedagogy, and activism?” and Nicole Aljoe offered a response to this inquiry: “How might Black Studies show a history in this constructed period not constituted by whiteness?”